2010
DOI: 10.1063/1.3454783
|View full text |Cite
|
Sign up to set email alerts
|

Infrared-wave number-dependent metal–insulator transition in vanadium dioxide nanoparticles

Abstract: We have studied the metal–insulator transition (MIT) taking place at 340 K in vanadium dioxide nanoparticles. A peculiar nanosize effect on the 10-nm-sized VO2 nanoparticles is reported. While the infrared transmittance at high wave numbers displayed a broad transition behavior, the magnetic susceptibility and infrared transmittance at low wave numbers showed a sharp first-order MIT. Our results suggest that the size effect on the MIT is due to the surface region while the core region undergoes the same MIT as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The MIT in VO 2 is usually associated with changes in magnetic susceptibility (χ) due to the electronic and structure changes . Klein predicted that it is possible to induce the MIT of VO 2 by applying a strong enough magnetic field .…”
Section: Magnetic Field Stimulated Devicesmentioning
confidence: 99%
“…The MIT in VO 2 is usually associated with changes in magnetic susceptibility (χ) due to the electronic and structure changes . Klein predicted that it is possible to induce the MIT of VO 2 by applying a strong enough magnetic field .…”
Section: Magnetic Field Stimulated Devicesmentioning
confidence: 99%
“…Even in other nano Mott transition materials, it is a common result for SMT. [16,34] This phenomenon partly affects the infrared filtering effect of nano Ti 2 O 3 . Here, we try to explain it theoretically.…”
Section: Why Transmittance Does Not Reduce To Zeromentioning
confidence: 99%
“…The transmittance changes of nano Ti 2 O 3 in the infrared region during the SMT are found to be sensitive to the wavelength, which could provide a new filtering method and meet the current requirement of infrared filtering materials mentioned above. Both conventional and nano Mott transition materials have been widely investigated before, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] but the differences in SMT between them have never been carefully studied. The nano Ti 2 O 3 specimens are found to go through the SMT in wide temperature ranges, the width of which is related to the grain size distributions.…”
Section: Introductionmentioning
confidence: 99%
“…5 At high temperatures, a large decrease in the transmittance is manifest, attributable to fast electron hopping between the V 4þ and V 5þ sites. 10,14 The C-H stretching region of 2800-3000 cm À1 , expanded in the inset of Fig. 2, reveals the presence of four distinct peaks assigned to methylene and methyl stretching modes.…”
mentioning
confidence: 98%
“…7 Among the vanadium oxide compounds, vanadium dioxide (VO 2 ) has long been studied for its first-order metal-insulator transition at $340 K, undergoing a drastic change in the electric, magnetic, and optical properties. [8][9][10] In previous works, electron spin resonance study of VO x -NTs revealed anomalies attributable to structural phase transitions and fast electron hopping motion among the vanadium sites at high temperatures. 6 In this work, we have investigated the phase transitions in VO x -NTs by using the Fourier-transform infrared (FT-IR) spectroscopy.…”
mentioning
confidence: 99%